Corroles and corrole/transferrin nanoconjugates as candidates for sonodynamic therapy. Issue 85 (8th October 2019) - Sharma, Vinay Kumar; Mahammed, Atif; Soll, Matan; Tumanskii, Boris; Gross, Zeev
Abstract : We report corroles as good agents for utilizing the otherwise harmless sonication of aqueous solutions as a tool for creating highly cytotoxic singlet oxygen, and demonstrate cancer cell killing via this approach. Abstract : We report the utility of water-soluble corroles and also protein-coated nanoparticles (NPs) of lipophilic corroles as potent candidates for sonodynamic therapy (SDT), through the detection and quantification of the singlet oxygen that is produced by the ultrasonic irradiation of their aqueous solutions. Preliminary results on a cancer cell line provide evidence for the true utility of the NPs for SDT.